1986
DOI: 10.1111/j.1365-2222.1986.tb01995.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal food antigen avoidance during pregnancy and lactation on incidence of atopic eczema in infants

Abstract: Abstract. One hundred and twenty‐one women with history of a previous child with atopic disease were randomly allocated during the next pregnancy to antigen avoidance or control groups. Dietary advice consisted of almost complete exclusion of milk and dairy products, egg, fish, beef and peanut throughout pregnancy and lactation. A total of 109 completed the study. Maternal antigen avoidance was associated with reduced occurrence of atopic eczema and the skin involvement was less extensive and milder. The bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(70 citation statements)
references
References 23 publications
2
67
1
Order By: Relevance
“…The risk reduction was more pronounced in children with a first-degree positive family history of atopic disease [pooled odds ratio (OR) 0.58, 95% confidence interval (CI) 0.41–0.92] than in those not restricted to those with a positive family history [OR 0.84 (0.59–1.19)]. The impressive results in high-risk children are likely to be biased, however, by the inclusion of the three studies by Chandra et al [3,24,25,26,27,28] – all of which reported large and statistically significantly increased risks in artificially fed infants – since their work has been clouded by suspicion of data fabrication.…”
Section: Atopic Dermatitismentioning
confidence: 82%
See 1 more Smart Citation
“…The risk reduction was more pronounced in children with a first-degree positive family history of atopic disease [pooled odds ratio (OR) 0.58, 95% confidence interval (CI) 0.41–0.92] than in those not restricted to those with a positive family history [OR 0.84 (0.59–1.19)]. The impressive results in high-risk children are likely to be biased, however, by the inclusion of the three studies by Chandra et al [3,24,25,26,27,28] – all of which reported large and statistically significantly increased risks in artificially fed infants – since their work has been clouded by suspicion of data fabrication.…”
Section: Atopic Dermatitismentioning
confidence: 82%
“…In fact, the effect actually appeared to be stronger in unselected children [summary OR 0.68 (0.47–0.99)] than in those with a positive family history [OR 0.87 (0.48–1.58)]. Of note, Chandra’s studies [24,25,26,27,28] did not report on this atopic outcome.…”
Section: Allergic Rhinitismentioning
confidence: 85%
“…In addition to a positive family history, total cord blood IgE (CB-IgE) was reported to be a useful predictive factor [3][4][5][6], Despite many rigorous studies, recent reports have failed to confirm that total CB-IgE levels predict atopic manifestations in infants [7][8][9][10][11], Prevention is generally based on the identification and elimination of the allergic substances which cause allergic reactions. Some studies indi cated that avoidance of highly allergenic food during pregnancy and/or lactation dimin ished the number of atopic manifestations during infancy [12,13]. In fact, we experience that the prevention of milk allergy in infants is, in some cases, effective when the pregnant mother takes less milk during pregnancy and breast-feeding.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study examined the effects of combined maternal and infant dietary restrictions. In this study, infants with allergic siblings were identified, the mother's diet was restricted (no milk, eggs, fish, beef, or peanuts) during the third trimester of pregnancy and lactation, and infants were either exclusively breast-fed for 5-6 months or ate an unrestricted diet (13). At the 1-year follow-up visit, the group of children with the restricted diet tended to have a lower prevalence of eczema, and if eczema was present, its severity was significantly reduced.…”
Section: Figurementioning
confidence: 99%